LA LEY ORGÁNICA DE APOYO HUMANITARIO Y SU INCIDENCIA EN EL DERECHO CONSTITUCIONAL AL TRABAJO. - Caguana Chimborazo, Klever Rumaldo (2023)
The work, considered as an intrinsic people right, is based on how human being satisfy their needs from the most basic looking for a better status. Labor rights, since their institutionalization, have always been progressive, as mandated by Constitution. In the present research, it is analyzed that, with Organic Law issuance of Humanitarian Support, far from being beneficial for workers, it rather places them in a "checkmate" position, worried about losing their job in a kind of threat, so there is no other option than accept reduction in their working hours and a reduction in their remuneration. For this fact, books and articles were reviewed and analyzed, in addition, the institutionalization of constitutional principles and labor rights from the beginning of the republic Ecuador history was analyzed and had an affectation on rights progress. Through qualitative methodology, of a documentary bibliographic type, it was evidenced that LOAH violated progressivity principle and work right, in 2020 year, date on when aforementioned law was issued, protected by Covid 2019 pandemic, observing public policy regression by workers State, failing to observe the guarantee precept that is required by Constitution and international treaties.